Physician perceived barriers and facilitators for self-measured blood pressure monitoring- a qualitative study. - Saahith Gondi (Public Library of Science (PLoS), 2021)
Introduction Improving hypertension management is a national priority that can decrease morbidity and mortality. Evidence-based hypertension management guidelines advocate self-measured BP (SMBP), but widespread implementation of SMBP is lacking. The purpose of this study was to describe the perspective of primary care physicians (PCPs) on SMBP to identify the barriers and facilitators for implementing SMBP. Methods We collected data from PCPs from a large health system using semi-structured interviews based on the Theoretical Domains Framework (TDF). Responses were recorded, transcribed, and qualitatively analyzed into three overarching TDF domains based on the Behavior Change Wheel (BCW): 1) Motivation 2) Opportunity and 3) Capabilities. The sample size was based on theme saturation. Results All 17 participating PCPs believed that SMBP is a useful, but underutilized tool. Although individual practices varied, most physicians felt that the increased data points from SMBP allowed for better hypertension management. Most felt that overcoming existing barriers would be difficult, but identified several facilitators: physician support of SMBP, the possibility of having other trained health professionals to assist with SMBP and patient education; improving patient engagement and empowerment with SMBP, and the interest of the health system in using technology to improve hypertension management. Conclusion PCPs believe that SMBP can improve hypertension management. There are numerous barriers and facilitators for implementing SMBP. Successful implementation in clinical practice will require implementation strategies targeted at increasing patient acceptability and reducing physician workload. This may need a radical change in the current methods of managing hypertension.